2018
DOI: 10.1002/anie.201802962
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Reductive Carbocyclization Using Engineered Ene Reductases

Abstract: Ene reductases from the Old Yellow Enzyme (OYE) family reduce the C=C double bond in α,β‐unsaturated compounds bearing an electron‐withdrawing group, for example, a carbonyl group. This asymmetric reduction has been exploited for biocatalysis. Going beyond its canonical function, we show that members of this enzyme family can also catalyze the formation of C−C bonds. α,β‐Unsaturated aldehydes and ketones containing an additional electrophilic group undergo reductive cyclization. Mechanistically, the two‐electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 71 publications
2
47
0
3
Order By: Relevance
“…Members of the enzyme families collectively called ene reductases (ERs) are effective biocatalysts for the stereoselective trans and—in rare cases— cis hydrogenation of activated alkenes, thus complementing chemical cis hydrogenations by using chiral rhodium or ruthenium phosphines (Knowles and Noyori, Nobel Prize in Chemistry 2001) . Recently, the canonical function of ene reductases was further expanded by enzyme engineering to include asymmetric reductive carbocyclization, which yields chiral cyclopropanes …”
Section: Introductionmentioning
confidence: 99%
“…Members of the enzyme families collectively called ene reductases (ERs) are effective biocatalysts for the stereoselective trans and—in rare cases— cis hydrogenation of activated alkenes, thus complementing chemical cis hydrogenations by using chiral rhodium or ruthenium phosphines (Knowles and Noyori, Nobel Prize in Chemistry 2001) . Recently, the canonical function of ene reductases was further expanded by enzyme engineering to include asymmetric reductive carbocyclization, which yields chiral cyclopropanes …”
Section: Introductionmentioning
confidence: 99%
“…Flavin-dependent 'ene'-reductases (EREDs) are substrate promiscuous oxidoreductases widely used in chemical synthesis for the stereoselective reduction of activated alkenes (14). Mechanistically, the reduction occurs via hydride transfer from the flavin hydroquinone (FMN hq ) to the electrophilic β-position of the alkene (15,16). In other protein scaffolds, such as ferredoxin reductase or P450 reductase, flavin effects the reduction via two single electron transfers (17).…”
mentioning
confidence: 99%
“…Generally, the ene-reductases, depending on whether the process takes place in eukaryotes or prokaryotes, utilize NADPH or FMNH2 to reduce electron-deficient alkenes, coaxed along by some simultaneous Lewis acidic coordination to a polar function, such as an ester, ketone or aldehyde. Synthetically, it has been demonstrated that the ene-reductases are competent at forming C–C bonds [77]. However, a brief glance at 16 reveals that the reacting termini cannot be activated in a similar manner as above.…”
Section: Resultsmentioning
confidence: 99%